Surgically‐treated hemoptysis and alveolar hemorrhaging resulting from severe mitral regurgitation: A case report. Issue 2 (13th February 2023) - Yamaguchi, Daisuke; Tokui, Toshiya; Narukawa, Takahiro; Murakami, Masahiko; Sekoguchi, Tomotake; Inoue, Ryosai; Hirano, Koji; Maze, Yasumi; Ito, Hisato
Abstract: Cardiac etiologies of hemoptysis are less common. One such etiology includes mitral regurgitation. In patients with hemoptysis and unilateral consolidation, careful chest auscultation and cardiac assessment may assist in making an early diagnosis. Abstract : This case suggests that MR can cause hemoptysis with unilateral pulmonary opacity. In patients with bloody sputum and unilateral consolidation, careful chest auscultation and cardiac assessment may lead to an early diagnosis.